IMF Staff papers : Volume 26 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1979)
This IMF Staff Paper highlights recent developments in monetary models of exchange rate determination. The seminal contributors to the monetary approach to the balance of payments suggested that the approach could be applied to a flexible exchange rate regime with only minor modifications. Several characteristics of recent exchange rate behavior, however, are against the traditional approach. These include persistent deviations from purchasing power parity, the large variance of short-term exchange rate movements, and the importance of speculation in the determination of the exchange rate. Although maintaining the emphasis of early monetary models on the integration of international asset markets and the stability of the money demand function, the new approaches also account for deviations from purchasing power parity, the endogenous determination of the interest rate, and the possibility that national currencies are close substitutes in a portfolio of currencies. An integrated model, which is capable of empirical verification, is also presented.